Hubungan HUBUNGAN ANTARA SIKAP SABAR DAN HUSNUDZON DENGAN MANAJEMEN STRES PADA MAHASISWA FAKULTAS KEDOKTERAN - Shina Samanda Alam; Rochman Basuki; Chamim Faizin (Jurnal Komunitas Farmasi Nasional, 2022)
Stress is something that must be addressed and resolved immediately. If this cannot be handled, it will cause a disturbance in the completion of the work.1 Stress management actions in dealing with stress can occur during the lecture process. This research is quantitative, analytical observational with a cross-sectional approach. The instrument used is a questionnaire consisting of patience, humility, and stress management. Bivariate analysis of patient attitude with stress management and husnudzon attitude with stress management using Spearman correlation test. The research sample was students of the Faculty of Medicine, University of Muhammadiyah Semarang, Class of 2020, which were taken using the Simple Random Sampling technique. There was a significant relationship with the direction of the positive correlation and the strength of the correlation is very strong. Patience with stress management results in a p-value of 0.000 and a correlation of 0.984, while husnudzon's attitude toward stress management results in a p-value of 0.000 and a correlation of 0.856. The better the attitude of patience and husnudzon attitude, the higher the ability to manage stress, and vice versa.